HONRA E HONESTIDADE NA METAFÍSICA DOS COSTUMES - PINZANI, Alessandro (Faculdade de Filosofia e Ciências, 2017)
This paper discusses some central notions of Kant’s Metaphysics of Morals. It claims that – although they are innate – dignity, external freedom and life are not something that ought to be granted unconditionally to individuals; rather individuals themselves should prove that they deserve to keep them, by acting in such a way that allows them to maintain their innate honesty and honour. In order to defend this interpretation, the paper analyses especially the connection between these two last concepts (in German: Ehre and Ehrbarkeit) both in the Doctrine of Law and in the Doctrine of Virtue.